Guest Editorial: Learning Experience Design: Embodiment, Gesture, and Interactivity in XR - Ioannou, Andri; Bhagat, Kaushal Kumar; Johnson-Glenberg, Mina C. (My University, 2021)
The concepts of embodiment and embodied learning are gaining traction in the field of education. This special issue aims to synthesize current knowledge on the design and evaluation of learning in immersive and embodied learning environments, mediated by XR (eXtended Reality) technologies. Of the 14 invited submissions, six (6) were finally accepted for publication. The collection of works in this special issue provides insights on best practices for learning experience design, based on systematic or empirical data and analysis on learning outcomes or processes.
Keywords: XR; AR; VR; MR; Extended reality; Virtual reality; Augmented reality; Mixed reality; Embodied learning; Immersive learning; Learning environments